Laparoendoscopic Single-Site Hysterectomy: A Single Surgeon Experience in a Tertiary Hospital - Gokhan Demirayak; Onur Guralp; Mustafa Yildiz; Cihan Comba; Veli Mihmanli; Isa Aykut Ozdemir (Medical Network, 2019)
Objective: To evaluate the clinical and surgical outcomes of the total hysterectomy cases performed with the laparoendoscopic single site surgery. Study Design: A total of 24 women who underwent total hysterectomy by the laparoendoscopic single site technique due to benign gynecological disorders were retrospectively evaluated. The duration of the operation, estimated blood loss, weight of the uterus, intra- and postoperative complications, pre- and postoperative day 1 hemoglobin and hematocrit levels, postoperative 6- and 24-hour visual analogue scale scores, duration of hospital stay, and postoperative complications were evaluated. Results: The mean total operation time was 112.1±24 minutes. The average time between the umbilical incision and starting the hysterectomy was 10±2.1 minutes. Estimated blood loss was 50±25 ml. The average duration of the hospital stay was 1.5±0.4 days. The mean uterus weight was 135 g. The mean difference between the pre- and postoperative hemoglobin values was 1.1 g/dl. The mean visual analogue scale scores were 4.1 (0-7) and 1.9 (0-4) in 6- and 24-hour postoperative periods. None of the women had an intraoperative complication. One patient (4.2%) had a port site hernia 6 months after the operation. Conclusion: The total hysterectomy with laparoendoscopic single site technique is a reasonable method in selected patients with similar safety and feasibility, especially for women who prefer a single incision in umbilicus. The patient should be informed before the operation about potential complications such as a port-site hernia.